2022
DOI: 10.1002/kin.21619
|View full text |Cite
|
Sign up to set email alerts
|

Study on pyrolysis behavior and kinetics of waste plastics with spent FCC catalyst

Abstract: Pyrolysis is the most promising method for treating plastic waste since it can convert waste plastics into high value‐added products, which have significant application potential. In this study, kinetic and thermodynamic analyses of spent fluid catalytic cracking (FCC) catalysts were performed for testing their applicability in catalytic cracking of mixed plastics. Thermogravimetric analysis data were obtained at different heating rates under an inert atmosphere, and the synergistic effect between the mixed pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 49 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…It can be seen from Figure that there is only one severe weight loss stage in the pyrolysis process of PP, LDPE, PS, and PET, indicating that the pyrolysis process of these four plastics is completed in one step . Among them, the conversion rates of PP, LDPE, and PS are close to 100%, indicating that the three plastics are almost completely converted into pyrolysis oil and pyrolysis gas during the pyrolysis process, resulting in almost no formation of pyrolysis residues.…”
Section: Resultsmentioning
confidence: 95%
“…It can be seen from Figure that there is only one severe weight loss stage in the pyrolysis process of PP, LDPE, PS, and PET, indicating that the pyrolysis process of these four plastics is completed in one step . Among them, the conversion rates of PP, LDPE, and PS are close to 100%, indicating that the three plastics are almost completely converted into pyrolysis oil and pyrolysis gas during the pyrolysis process, resulting in almost no formation of pyrolysis residues.…”
Section: Resultsmentioning
confidence: 95%
“…A comparison of the experimental and model-predicted data showed a good agreement except at the high conversions (Figure 7). Shan et al (2023) 57 also found Avrami-Erofeev equation to satisfactorily fit the catalytic degradation data of HDPE, PP and PS. Das and Tiwari (2017) 7 and Zhang et al (2022) 46 reported a two-dimensional contractingcylinder model for the degradation of HDPE and LDPE and a three-dimensional contracting-sphere model for PP.…”
Section: Identification Of Reaction Rate Model Using a Master Plotmentioning
confidence: 92%